Ultra-high performance concrete material with compressive strength of 250MPa or above as well as preparation method and application of ultra-high performance concrete material

By adding fly ash and microbeads to ultra-high performance concrete and adopting a combined maintenance method, the problems of compressive strength improvement and resource waste in the existing technology are solved, and high-strength, low-carbon and low-energy consumption are achieved. High-performance concrete preparation.

CN119118604APending Publication Date: 2024-12-13SUZHOU CONCRETE CEMENT PROD RES INST
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411365714.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing ultra-high performance concrete has problems of wasted resources and reduced working performance in improving compressive strength, and traditional autoclaved maintenance consumes a lot of energy and is harsh in conditions, making it difficult to promote.

Method used

在超高性能混凝土中同时添加需水量低的粉煤灰和微珠,并控制其用量,调整纳米二氧化硅的用量,采用组合养护方式,包括标准养护、蒸汽养护和干热养护,促进托 The formation of ermullite and hard silicate improves the compactness and compressive strength of the matrix.

Benefits of technology

It significantly improves the compressive strength of ultra-high performance concrete, reduces carbon emissions, has a simple process and low energy consumption, and meets the needs of high-strength and low-cost building materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118604A_ABST
    Figure CN119118604A_ABST
Patent Text Reader

Abstract

The invention relates to ultra-high performance concrete with compressive strength of 250MPa or above as well as a preparation method and application of the ultra-high performance concrete. The raw materials comprise a binding material, nano silicon dioxide, a water reducing agent, water and steel fibers, the cementing material comprises cement, silica fume and fine aggregate; the cementing material further comprises fly ash and microbeads, the water demand ratio of the fly ash is 95% or below, and the water demand ratio of the microbeads is 98% or below; on the basis of the total mass of the cementing material and the nano silicon dioxide, the mass of the fly ash accounts for 4%-6%, the mass of the microbeads accounts for 4%-6%, and the mass of the nano silicon dioxide accounts for 0.5%-1.4%. The compressive strength of the ultra-high performance concrete material can reach up to 250 MPa or above, and high requirements of special building materials can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of concrete, and in particular relates to an ultra-high performance concrete with a compressive strength of more than 250 MPa and a preparation method and application thereof. Background Art

[0002] With the continuous development of engineering construction such as roads and bridges, energy, and national defense and military in my country, the requirements for building materials are getting higher and higher. For example, the main structure of the terminal building of Daxing International Airport is built with ultra-high performance concrete (Ultra High Performance Concrete, referred to as UHPC), and the compressive strength of some components reaches 120MPa. The main building structure of the Shanghai Tower uses a large amount of UHPC, with a strength of 150MPa. The strength grade of UHPC in the standard specifications is also gradually increasing. For example, DB13 / T 2946-2019 "Technical Code for Preparation and Engineering Application of Ultra-High Performance Concrete" states that the highest mechanical property grade of ultra-high performance concrete is UC200-4, and the compressive strength is ≥200MPa. High-strength and lightweight development has become the development trend of construction engineering. At the same time, the growth of special projects such as the national nuclear industry, marine development, and military construction has also increased the demand for high-strength concrete.

[0003] UHPC combines the excellent strength and long-term durability of high-strength concrete, the fluidity and filling properties of self-compacting concrete, and the high toughness and strain hardening properties of fiber-reinforced concrete. It is usually made of cement, silica fume, fly ash, mineral powder, water reducer, steel fiber, fine aggregate and other materials. Compared with ordinary concrete, UHPC has better performance in all aspects. The compressive strength of common ultra-high performance concrete is between 120MPa-180MPa, which is about 3-6 times that of ordinary concrete. Its ductility and energy absorption are about 300 times higher than that of ordinary concrete. In addition, ultra-high performance concrete is almost impermeable to carbon dioxide, chlorides and sulfates. Its excellent mechanical properties and durability make ultra-high performance concrete components have the advantages of high strength, light weight, and low life cycle cost. Therefore, it is widely used in the construction of bridges, tunnels, wind turbine towers, nuclear power plants and other projects, and has good development and application prospects.

[0004] In order to meet the needs of building structures to develop in the direction of lightweight and high strength, many researchers at home and abroad have conducted extensive research on the optimization of the mechanical properties of UHPC. In the existing technology, supplementary modified materials are often used to promote volcanic ash reaction and optimize pore structure, high-doped steel fibers are used to improve crack resistance and tensile properties, and autoclaving is used to promote the formation of high-strength tobermorite and xonotlite. However, the effect of improving strength through material design is limited. Too high a dosage of steel fibers will lead to a decrease in working performance and thus affect the density of the matrix. The energy consumption of autoclaving is large, and the maintenance equipment and site construction conditions are harsh, making it difficult to promote and apply. Therefore, in order to promote the development of construction projects in the direction of high quality and large-scale, it is urgent to seek a high-strength building material with a simple preparation process. Summary of the invention

[0005] In view of the deficiencies of the prior art, one of the purposes of the present invention is to provide an improved ultra-high performance concrete material, whose compressive strength can be as high as 250 MPa or more, which can meet the high requirements of special building materials.

[0006] Another object of the present invention is to provide a method for preparing an ultra-high performance concrete material, which has a simple process and can significantly improve the compressive strength of the ultra-high performance concrete material.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] A super high performance concrete, the raw materials of which include cementitious material, nano silicon dioxide, water reducing agent, water and steel fiber; the cementitious material includes cement, silica fume and fine aggregate; the cementitious material also includes fly ash and micro beads, the water demand ratio of the fly ash is less than 95%, and the water demand ratio of the micro beads is less than 98%; based on the total mass of the cementitious material and the nano silicon dioxide, the mass of the fly ash accounts for 4%-6%, the mass of the micro beads accounts for 4%-6%, and the mass of the nano silicon dioxide accounts for 0.5%-1.4%.

[0009] Common UHPC uses a high amount of cement and silica fume to achieve the most compact packing design. However, too high a content of cement and silica fume not only cannot fully participate in the hydration reaction, resulting in a waste of resources, but also leads to a decrease in the system's working performance and increased shrinkage in the later stage. Adding nano-silica to UHPC helps to promote the formation of gel in the hydration product and optimize the pore structure. However, nano-scale materials have a large specific surface area and are not easy to disperse, which has an adverse effect on the working performance of UHPC. The inventors of this application have found through a large number of experimental studies that by adding fly ash and microbeads with relatively low water requirements to UHPC materials at the same time, and controlling the amount of fly ash and microbeads within a specific range at the same time, and adjusting the amount of nano-silica, the volcanic ash effect, filling effect and ball effect of the admixture can be fully utilized, which plays a role in improving the matrix density, improving the working performance, especially significantly improving the compressive strength and flexural strength of UHPC, and reducing carbon emissions.

[0010] In some specific embodiments, the water demand ratio of the fly ash is 90%-95%.

[0011] In some embodiments, the water requirement ratio of the microbeads is 90%-98%.

[0012] In the present invention, the water demand ratio refers to the ratio of the water consumption when the fluidity of the mineral admixture mortar reaches the same fluidity as the reference mortar to the water consumption of the reference mortar.

[0013] In some specific embodiments, in the raw materials of the ultra-high performance concrete, the total mass of the cementitious material and the nano-silicon dioxide is 100 parts, the water reducer is 1.6-2.1 parts, the water is 7-8 parts, and the steel fiber is 7-11 parts; wherein, based on the total mass of the cementitious material and the nano-silicon dioxide, in terms of weight percentage:

[0014]

[0015] In some specific embodiments, the mass of the nano-silicon dioxide is 10%-23% of the mass of the silica fume.

[0016] Preferably, the mass of the nano-silicon dioxide is 17%-23% of the mass of the silica ash.

[0017] In some specific embodiments, the nano-silica is hydrophilic fumed nano-silica, and the particle size is 0.01-0.2 μm.

[0018] In some specific embodiments, the cement is silicate cement or ordinary silicate cement, and the strength of the cement is not less than 52.5 MPa. The silicate cement or ordinary silicate cement is defined according to the standard classification in GB 175 "General Purpose Portland Cement".

[0019] In some specific embodiments, the silica fume has a silica mass content of ≥95%.

[0020] In some specific embodiments, the particle size of the silica fume is 0.2-200 μm.

[0021] In some specific embodiments, the water reducer is a polycarboxylate water reducer.

[0022] In some specific embodiments, the solid content of the water reducing agent is greater than 25%.

[0023] In some specific embodiments, the water reducing agent has a water reducing rate of 30% or more.

[0024] In some specific embodiments, the steel fiber is a copper-plated hook-end steel fiber.

[0025] In some specific embodiments, the length of the steel fiber is 10-20 mm, preferably 13-20 mm.

[0026] In some specific embodiments, the diameter of the steel fiber is 0.1-0.4 mm, preferably 0.25-0.4 mm.

[0027] In some specific embodiments, the fine aggregate comprises a mixture of four quartz sands of different mesh sizes, and the mesh size is 30-120 meshes.

[0028] In some specific embodiments, the fine aggregate includes 30 mesh, 50 mesh, 60 mesh, and 120 mesh quartz sand. In terms of weight percentage, the fine aggregate includes 35%-40% of 30 mesh quartz sand, 10-15% of 50 mesh quartz sand, 35%-40% of 60 mesh quartz sand, and 10%-15% of 120 mesh quartz sand.

[0029] In some specific embodiments, the ultra-high performance concrete is prepared by a preparation method comprising the following steps: premixing the nano-silica with the fine aggregate to obtain a premix; dry mixing the premix with the remaining cementitious material, adding water and a water reducer to mix; adding steel fiber to obtain an ultra-high performance concrete mixture; casting the ultra-high performance concrete mixture, and performing standard curing, steam curing and dry heat curing in sequence after demolding to obtain the ultra-high performance concrete.

[0030] The present invention also provides a method for preparing the aforementioned ultra-high performance concrete, the preparation method comprising the following steps: premixing the nano-silicon dioxide with the fine aggregate to obtain a premix; dry mixing the premix with the remaining cementitious material, adding water and a water reducer to mix; adding steel fiber to obtain an ultra-high performance concrete mixture; casting and molding the ultra-high performance concrete mixture, and performing standard curing, steam curing and dry heat curing in sequence after demolding to obtain the ultra-high performance concrete.

[0031] In the present invention, standard curing refers to curing in a high humidity environment at room temperature, the temperature is (20±2)° C., and the humidity is usually above 95%.

[0032] In some specific embodiments, the adding of water and water reducing agent for mixing is specifically as follows: firstly adding 70%-90% by mass of water and all the water reducing agent, stirring and mixing, and then adding the remaining water and continuing to stir.

[0033] In some specific embodiments, the adding of water and water reducing agent for mixing is specifically as follows: first adding 70%-90% by mass of water and all the water reducing agent, stirring and mixing for 2-4 minutes, and then adding the remaining water and continuing to stir for 1-2 minutes.

[0034] In some specific embodiments, the standard curing is carried out at a temperature of (20±2)° C. and a humidity of 95% or more.

[0035] In some specific embodiments, the standard curing time is 48-72 hours.

[0036] In some specific embodiments, the steam curing temperature is 80-100°C.

[0037] In some specific embodiments, the steam curing time is 48-60 hours.

[0038] In some specific embodiments, the dry heat curing temperature is 165-185°C.

[0039] In some specific embodiments, the dry heat curing time is 18-24 hours.

[0040] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0041] The present invention adds fly ash and microbeads with relatively low water demand to the UHPC material at the same time, controls the amount of fly ash and microbeads within a specific range, and adjusts the amount of nano-silicon dioxide, so as to give full play to the volcanic ash effect, filling effect and ball effect of the admixture, improve the matrix density, improve the working performance, especially significantly improve the compressive strength and flexural strength of UHPC, and reduce carbon emissions. The compressive strength of the ultra-high performance concrete material of the present invention can be as high as 250MPa or more, which can meet the high requirements of special building materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 is the particle size distribution and close packing curve of each raw material in Example 1;

[0043] Figure 2 This is the flexural failure morphology of the specimen in Example 1;

[0044] Figure 3 This is the compressive failure morphology of the specimen in Example 1;

[0045] Figure 4 The figures are a comparison of the dispersibility of nano-silicon dioxide under different mixing methods, where (a) nano-silicon dioxide, cementitious material and quartz sand are premixed at the same time; (b) nano-silicon dioxide and quartz sand are premixed; (c) the premixed nano-silicon dioxide and quartz sand are dry-mixed with the cementitious material. DETAILED DESCRIPTION

[0046] Common UHPC uses a high amount of cement and silica fume to achieve the most compact packing design. However, too high a content of cement and silica fume not only cannot fully participate in the hydration reaction, resulting in a waste of resources, but also leads to a decrease in the system's working performance and increased shrinkage in the later stage. Adding nano-silica to UHPC helps promote the formation of gel in the hydration product and optimize the pore structure. However, nano-scale materials have a large specific surface area and are not easy to disperse, which has an adverse effect on the working performance of UHPC.

[0047] The present invention simultaneously adds fly ash and microbeads with relatively low water demand into the UHPC material, controls the dosage of the fly ash and microbeads within a specific range, and adjusts the dosage of nano-silicon dioxide, so as to give full play to the volcanic ash effect, filling effect and ball effect of the admixture, improve the matrix density, improve the working performance, especially significantly improve the compressive strength and flexural strength of the UHPC, and reduce carbon emissions.

[0048] The present invention significantly improves the dispersibility of nano silicon dioxide by premixing nano silicon dioxide with fine aggregate and then adding other materials for mixing. The mixture obtained by the method has no obvious nano silicon dioxide agglomeration phenomenon, thereby significantly improving the homogeneity and density of the UHPC slurry, promoting the development of strength, and improving the strength of the final concrete.

[0049] The present invention adopts a combined curing method. This method develops a certain early strength of the UHPC matrix through standard curing. Since the UHPC microstructure is very dense, the heat released by the hydration reaction causes the water or air inside the closed pores to expand due to heat, and the pressure inside the pores increases. At this time, the coordinated steam curing puts the UHPC under high temperature and high pressure, which promotes the formation of tobermorite and xonotlite crystals, and the dry heat curing accelerates the formation process of tobermorite and xonotlite crystals, so that the strength is rapidly developed. Compared with traditional direct autoclave curing or standard curing, the concrete of the present invention has obvious strength improvement effect, low energy consumption and low carbon emissions.

[0050] The technical solution of the present invention is described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand and implement the technical solution of the present invention, but the present invention is not limited to the scope of the examples.

[0051] Unless otherwise specified, the raw materials used in this application can be obtained from commercial sources.

[0052] Example 1

[0053] This embodiment provides an ultra-high performance concrete, and its raw material formula (by weight) is shown in Table 1.

[0054] Among them, the silica ash is fully encrypted silica ash, with a silicon content of ≥95%, D 50 The surface area is 6.04 μm and the specific surface area is 19800 m 2 / kg.

[0055] The fly ash is Class I fly ash, with a water requirement ratio of 93%, D 50 The diameter is 48.00 μm and the specific surface area is 395 m 2 / kg.

[0056] The water requirement ratio of microbeads is 95%, D 50 The surface area is 36.11 μm and the specific surface area is 483 m 2 / kg.

[0057] Nanosilica, D 50 0.20μm.

[0058] The steel fiber is a copper-plated end hook steel fiber with a length of 13 mm and a diameter of 0.25 mm.

[0059] The quartz sand is a mixture of four types according to weight percentage, including 30 mesh 21.1%, 50 mesh 4.9%, 60 mesh 21.1%, and 120 mesh 7.1%.

[0060] The water reducing agent is polycarboxylic acid water reducing agent with a solid content of 27% and a water reducing rate of 32%.

[0061] The particle size distribution and close packing curves of each raw material (target curve, actual curve of Example 1) are as follows: Figure 1 As shown, it can be seen that the stacking method of Example 1 is basically close to the target dense stacking method.

[0062] Prepared by the following method:

[0063] (1) Weigh each component according to weight percentage;

[0064] (2) Mix the weighed nano-silicon dioxide and quartz sand and dry-mix for 2 minutes to obtain a premix;

[0065] (3) Add the premixed material in (2) and the remaining cementitious materials (cement, silica fume, fly ash and microspheres) into a mixer and dry mix for 1 minute to fully mix;

[0066] (4) Add 80% of the water and all the water reducer into the mixer and stir for 4 minutes;

[0067] (5) Add the remaining 20% ​​water into the blender and continue blending for 2 minutes;

[0068] (6) adding steel fiber and stirring for 2 min to obtain a UHPC mixture;

[0069] (7) Pour the UHPC mixture into the mold in two pouring steps and vibrate to form the mixture, and demold the mixture after 24 hours.

[0070] (8) The demoulded specimens were cured at a temperature of 20±2°C and a humidity of ≥95% for 48 h, then cured in a steam curing oven at 90°C for 48 h, and then dry-cured in an oven at 185°C for 24 h.

[0071] Embodiment 2-5

[0072] This embodiment provides an ultra-high performance concrete, which is basically the same as Embodiment 1, except that the raw material formula is different and the curing process time is different, see Table 1 for details.

[0073] Comparative Examples 1-4

[0074] This comparative example provides a concrete, which is basically the same as Example 1, except that the raw material formula is different, see Table 1 for details. Specifically, Comparative Examples 1-2 change the content of components such as nano-silicon dioxide, Comparative Example 3 changes the content of components such as fly ash, and Comparative Example 4 changes the content of components such as microspheres.

[0075] Comparative Example 5

[0076] This comparative example provides a concrete, which is basically the same as Example 1, except that the water requirement ratio of the fly ash used in this comparative example is 95%, and the water requirement ratio of the microspheres is 98%.

[0077] Comparative Example 6

[0078] This comparative example provides a concrete, which is basically the same as Example 1, except that the mixing method of nano-silicon dioxide is different. Specifically, the preparation method of the concrete is as follows:

[0079] (1) Weigh each component according to weight percentage;

[0080] (2) Add the weighed nano-silicon dioxide, quartz sand, and the remaining cementitious materials (cement, silica fume, fly ash, and microbeads) into a mixer and dry mix for 2 minutes to fully mix;

[0081] (3) Add 80% of the water and all the water reducer into the mixer and stir for 4 minutes;

[0082] (4) Add the remaining 20% ​​of water and continue stirring for 2 minutes;

[0083] (5) adding steel fiber and stirring for 2 min to obtain a UHPC mixture;

[0084] (6) Pour the UHPC mixture into the mold, vibrate and shape it twice, and demold it after 24 hours;

[0085] (7) The demoulded specimens were cured at a temperature of 20±2°C and a humidity of ≥95% for 48 h, then cured in a steam curing oven at 90°C for 48 h, and then dry-cured in an oven at 185°C for 24 h.

[0086] Comparative Example 7

[0087] This comparative example provides a concrete, which is basically the same as Example 1, except that: the curing method in step (8) is different, and standard curing is not performed, and steam curing and dry heat curing are directly performed. Step (8) specifically comprises: placing the demoulded specimen in a steam curing box at 90° C. for 48 hours, and then dry-heat curing in an oven at 185° C. for 24 hours.

[0088] Comparative Example 8

[0089] This comparative example provides a concrete, which is basically the same as Example 1, except that: the curing method in step (8) is different, and dry heat curing is not performed, only standard curing and steam curing are performed. Step (8) specifically comprises: curing the demoulded specimen at a temperature of 20±2° C. and a humidity of ≥95% for 48 hours, and then curing it in a steam curing box at 90° C. for 48 hours.

[0090] Table 1 Raw material formulations and curing process parameters of each embodiment and comparative example (by weight)

[0091]

[0092] Performance testing

[0093] According to the method specified in GB / T 17671-2021, the compressive and flexural strengths of the ultra-high performance concrete specimens in each embodiment and comparative example were tested. The test results are shown in Table 2, where standard curing for 28 days refers to curing for 28 days according to the standard curing method, which is used as the basis for strength comparison.

[0094] Table 2 Performance test results

[0095]

[0096]

[0097] From the results in Table 2, it can be seen that based on the total mass of the cementitious material, nano-silicon dioxide and quartz sand, the compressive strength of the UHPC prepared by fully premixing with quartz sand and containing 1.4% nano-silicon dioxide after combined curing reaches 258.3MPa (Example 1). Compared with the specimen cured for 28 days, the compressive strength increases by 61.9%. The flexural and compressive failure forms are as follows: Figure 2 and Figure 3 As shown. Figure 2 It can be seen that the specimen failure process is ductile failure, and some steel fibers still bridge the two ends of the crack after failure. Figure 3It can be seen that the specimens after compressive damage are relatively intact, with only cracks and slag falling at the junction of the compression surface and the side. With the increase in the amount of silica fume and microspheres and the decrease in the amount of cement and fly ash (Example 2), the compressive strength of UHPC after standard curing and combined curing decreased, which was 2.1% and 2.2% lower than that in Example 1, respectively. When the amount of cement and fly ash was increased and the amount of silica fume and microspheres was reduced (Example 3), the compressive strength of the specimens after standard curing for 28 days and combined curing decreased by 6.0% and 0.9% respectively compared with Example 1. When the mortar-sand ratio was changed to 1:1.1, the compressive strength of the specimens decreased under different cementitious material particle composition conditions (Examples 4 and 5), but the strength after combined curing was higher than 250MPa.

[0098] When the amount of nano-silicon dioxide added is too little (Comparative Example 1), the compressive strength of the specimen after standard curing and combined curing decreases by 11.2% and 14.9% respectively compared with Example 1; when the amount is too much (Comparative Example 2), it decreases by 8.7% and 8.1% respectively; when the amount of fly ash is reduced (Comparative Example 3), the compressive strength of the specimen after standard curing and combined curing decreases by 7.4% and 7.7% respectively compared with Example 1; when the amount of microspheres is reduced (Comparative Example 4), it decreases by 11.4% and 9.1% respectively; if the water demand of the fly ash and microspheres used is relatively high (Comparative Example 5), the compressive strength after standard curing and combined curing decreases by 8.0% and 12.0% respectively compared with Example 1.

[0099] When nano-silica and quartz sand are not pre-mixed during the preparation of the UHPC mixture (Comparative Example 6), the strength of the prepared specimens after standard curing and combined curing decreases by 4.4% and 4.6%, respectively; or when 48 hours of standard curing is not performed before steam curing in the combined curing (Comparative Example 7), the compressive strength of the specimens after combined curing decreases by 9.9%; when the specimens after steam curing are not dry-heat cured (Comparative Example 8), the combined curing compressive strength decreases by 14.6% compared with Example 1.

[0100] From the above strength test results, it can be seen that under the synergistic effect of raw material composition design, control of nano-silica dosage, premixing with quartz sand, combined curing and other conditions, the prepared UHPC has good homogeneity and high compressive strength. Among them, nano-silica particles are finer, with a larger specific surface area, higher volcanic ash activity than silica fume, higher reaction degree and faster reaction rate with calcium hydroxide in cement matrix, and provide nucleation sites to promote the nucleation growth of CSH gel, so that the CSH chain length increases, which helps to improve the density of UHPC matrix. At the same time, the unreacted nano-silica particles fill the pores of the matrix, which is conducive to refining the pore structure and reducing the number of harmful pores.

[0101] like Figure 4As shown in (a), when nano-silicon dioxide is directly mixed with cementitious materials and quartz sand, due to the fineness of nano-silicon dioxide particles and low density, the electrostatic force generated by the friction with the cementitious material particles during the mixing process causes the nano-silicon dioxide particles to adsorb each other and agglomerate significantly. However, when nano-silicon dioxide is mixed with quartz sand in advance, the quartz sand effectively hinders the agglomeration process of nano-silicon dioxide, and the collision and friction between the quartz sand particles help to improve the dispersibility of nano-silicon dioxide, such as Figure 4 (b). Figure 4 As shown in (c), the dry mix obtained by this method is relatively uniform, without obvious particles and agglomeration, so the prepared UHPC has better homogeneity and higher density.

[0102] The combined curing process of Example 1 includes 48h standard curing, 48h steam curing and 24h dry heat curing. Since the initial stage, induction stage and acceleration stage of the UHPC hydration reaction usually occur in the first 3 days, CSH is generated and polymerized in large quantities during this process. Therefore, the 2d (48h) standard curing allows the early hydration reaction of UHPC to proceed fully, generating a certain amount of hydration products and forming a certain early strength. When the UHPC hydration reaction enters the decay period, the hydration reaction rate decreases, and the reaction is mainly diffusion-based. At this time, the high temperature conditions of steam curing help promote the hydration of unreacted raw material particles, thereby increasing the degree of reaction of UHPC. On this basis, the 185°C dry heat curing promotes the transformation of CSH gel into denser and harder tobermorite and hard calcium silicate, further stimulating the improvement of compressive strength.

[0103] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

[0104] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

Claims

1. An ultra-high performance concrete, wherein the raw materials of the ultra-high performance concrete include a cementitious material, nano-silicon dioxide, a water reducing agent, water and steel fiber; the cementitious material includes cement, silica fume and fine aggregate; characterized in that: The cementitious material also includes fly ash and micro beads, the water demand ratio of the fly ash is less than 95%, and the water demand ratio of the micro beads is less than 98%. Based on the total mass of the cementitious material and nano-silicon dioxide, the mass of the fly ash accounts for 4%-6%, the mass of the micro beads accounts for 4%-6%, and the mass of the nano-silicon dioxide accounts for 0.5%-1.4%.

2. The ultra-high performance concrete according to claim 1, characterized in that: The water requirement ratio of the fly ash is 90%-95%; and / or the water requirement ratio of the microbeads is 90%-98%.

3. The ultra-high performance concrete according to claim 1, characterized in that: In terms of weight, in the raw materials of the ultra-high performance concrete, the total mass of the cementitious material and the nano-silicon dioxide is 100 parts, the water reducer is 1.6-2.1 parts, the water is 7-8 parts, and the steel fiber is 7-11 parts; wherein, based on the total mass of the cementitious material and the nano-silicon dioxide, in terms of weight percentage:

4. The ultra-high performance concrete according to claim 1 or 3, characterized in that: The mass of the nano-silicon dioxide is 10%-23% of the mass of the silica fume; and / or the nano-silicon dioxide is hydrophilic gas-phase nano-silicon dioxide, and the particle size is 0.01-0.2 μm.

5. The ultra-high performance concrete according to claim 1 or 3, characterized in that: The cement is silicate cement or ordinary silicate cement, and the strength of the cement is not less than 52.5MPa; and / or the silica fume has a silica mass content of ≥95%, and / or the silica fume has a particle size of 0.2-200μm; and / or the water reducer is a polycarboxylate water reducer; and / or the solid content of the water reducer is greater than 25%; and / or the water reduction rate of the water reducer is greater than 30%.

6. The ultra-high performance concrete according to claim 1 or 3, characterized in that: The steel fiber is a copper-plated end hook steel fiber; and / or, the length of the steel fiber is 10-20 mm; and / or, the diameter of the steel fiber is 0.1-0.4 mm; and / or, the fine aggregate comprises a mixture of four quartz sands of different mesh sizes, and the mesh size is 30-120 mesh; preferably, the fine aggregate comprises quartz sands of 30 mesh, 50 mesh, 60 mesh, and 120 mesh, and in terms of weight percentage, the fine aggregate comprises 35%-40% of 30 mesh quartz sand, 10-15% of 50 mesh quartz sand, 35%-40% of 60 mesh quartz sand, and 10%-15% of 120 mesh quartz sand.

7. The ultra-high performance concrete according to claim 1 or 3, characterized in that: The ultra-high performance concrete is prepared by a preparation method comprising the following steps: premixing the nano-silicon dioxide with the fine aggregate to obtain a premix; dry-mixing the premix with the remaining cementitious material, adding water and a water reducer to mix; adding steel fiber to obtain an ultra-high performance concrete mixture; casting and molding the ultra-high performance concrete mixture, and performing standard curing, steam curing and dry heat curing in sequence after demoulding to obtain the ultra-high performance concrete.

8. A method for preparing ultra-high performance concrete according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: premixing the nano silicon dioxide with the fine aggregate to obtain a premix; dry mixing the premix with the remaining cementitious material, adding water and a water reducing agent to mix; adding steel fiber to obtain an ultra-high performance concrete mixture; casting and molding the ultra-high performance concrete mixture, and performing standard curing, steam curing and dry heat curing in sequence after demoulding to obtain the ultra-high performance concrete.

9. The method for preparing ultra-high performance concrete according to claim 8, characterized in that: The adding of water and water reducing agent for mixing is specifically as follows: the adding of water and water reducing agent for mixing is specifically as follows: first adding 70%-90% by mass of water and all the water reducing agent, stirring and mixing, and then adding the remaining water and continuing to stir; and / or, the standard curing is carried out at a temperature of 18-22°C and a humidity of more than 95%; and / or, the standard curing time is 48-72h; and / or, the steam curing temperature is 80-100°C; and / or, the steam curing time is 48-60h; and / or, the dry heat curing temperature is 165-185°C; and / or, the dry heat curing time is 18-24h.

10. Use of the ultra-high performance concrete according to any one of claims 1 to 7 in road repair.

Citation Information

Cited By

  • Ultra-high performance concrete as well as preparation method and application thereof

    CN120645294A